Personalized Feedback in Web Surveys: Does It Affect Respondents' Motivation and Data Quality? - Simon Kühne; Martin Kroh (Social Science Computer Review, 2018)
Web surveys technically allow providing feedback to the respondents based on their previous responses. This personalized feedback may increase respondents' motivation and possibly the accuracy of responses. While past studies mainly concentrate on the effects of providing study results on future response rates, thus far survey research lacks theoretical and empirical contributions on the effects of personalized, immediate, feedback on response behavior. To test this, we implemented a randomized trial in the context of the Berlin Aging Study II (BASE-II) in 2014, providing feedback regarding the respondents' personality tests (Big Five Personality Inventory) to a subgroup of the sample. Results show only moderate differences in response behavior between experimental and control groups. However, we find that respondents who received personalized feedback report higher levels of satisfaction with the survey.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer bundesweiten Konsortiallizenz in der Nachfolge einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. – This publication is with permission of the rights owner freely accessible due to an consortial licence (funded by the DFG, German Research Foundation) respectively
Keywords: 330; Personalized feedback; Web surveys; Online surveys; Measurement error; Survey satisfaction; Big Five Personality Inventory